Law And Ethic On The Copyright Of Artificial Intelligence Works In Indonesia : Hukum Dan Etika Atas Hak Cipta Karya Kecerdasan Buatan Di Indonesia - Ajeng Aditya Listyani; Maria Mu’ti Wulandari; Frida Nurrahma Masturi (DAS Institute, 2026)
Technological advances open up opportunities for development for the creation of an object. In its development, Artificial Intelligence technology is able to create and produce a product so that protection of Intellectual Property Rights of it is needed. Law Number 28 of 2014 concerning Copyright has not been able to accommodate the protection of Intellectual Property Rights of product that produced by Artificial Intelligence due to the unclarity of the creator. For this reason, a protection mechanism is needed for product that produced by Artificial Intelligence. This study aims to identify and analyze the legal construction of intellectual property rights for product that produced by artificial intelligence in Indonesia and forms of copyright protection for product that produced by artificial intelligence. This research is a normative juridical research with analytical descriptive research specifications. This research uses a statutory approach, concept approach and comparison approach. The data used are secondary data that obtained from literature studies. The data are presented with normative texts and analyzed by qualitative normative methods. The results show that the legal construction of intellectual property rights for product that produced by artificial intelligence in Indonesia needs to be developed so that the creators can get copyrights to their products. The implementation of the legal construction of Artificial Intelligence also need ethical part to it.